The Calibration and Performance Evaluation of Rainfall Simulator - Rahadi, Bambang; Soemarno, Soemarno; Masrevaniah, Aniek; Priyono, Sugeng (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Rainfall simulator is important for studying hydrology and erosion in laboratory. The most important parameter for studying the performance of rainfall simulator is rain intensity, drop size distribution, drop mass, drop impact velocity, and kinetic energy. They are evaluated by uniformity coefficient (UC) and distribution uniformity (DU). This research was aimed to study the functional performance of rainfall simulator including determination of the correlation between pressure with rainfall parameters (rain intensity, drop size distribution, and kinetic energy) and rainfall simulator performance evaluation based on uniformity coefficient and distribution uniformity. The data was analyzed by using linear regression and evaluated by uniformity coefficient and distribution uniformity.The result showed that pressure had linear relationship with rain intensity, diameter drop distribution, drop impact velocity, dropped mass, and kinetic energy. The coefficient uniformity (CU) of the pressure 2.5 psi-6.5 psi more than 80% and the distribution uniformity (DU) more than 70%. The rainfall simulator had better performance at the pressure of 2.5 psi than 6.5 psi.Keywords: rainfall, simulator, performance